IMPLEMENTASI ANALISIS SWOT (STRENGTH, WEAKNESS, OPPORTUNITIES, AND THREAT) DALAM STRATEGI PEMASARAN PRODUK PADA PT ADIB GLOBAL FOOD SUPPLIES SURABAYA (Jurnal Bisnis Indonesia, 2022)
PT Adib Global Food Supplies Surabaya is companies is a refrigeration truck transportation service (Cold Chain) and has meat, vegetable, fruit, marine and fresh fish products, processed / frozen food and dried materials for the domestic market segment. In the increasingly stringent development of the business world, especially in the field of food, which is constantly developing and very flexible, the company must be able to create a strategy so that it can get a positive assessment from consumers and be able to create an attraction for customers to make purchases again and continously. This study aims to enable the company to be able to determine the strengths, weaknesses, threats and opportunities aspects of the company as well as to know what strategies should be implemented in order to reach the maximum point in its business, both in terms of the level of consumer loyalty, competitiveness, and so on. The method used is descriptive with data collection through observation, interviews, literature study and the Internet. The data analysis technique used is descriptive qualitative analysis techniques. The result of this research is that PT Adib Global Food Supplies Surabaya has a weakness, namely the lack of experts for product development.Keywords : SWOT Analysis, Marketing Strategy, Product Marketing  DOI : https://doi.org/10.33005/jbi.v13i1.3079